Security Audit of The Public Sector Application Using COBIT 5 and ITIL V4 Framework - Julianti Alavio; Rima Mawarni; Sulas minarti (LPPM Universitas Islam 45 Bekasi, 2024)
The use of information system-based applications has become commonplace in various sectors, including government agencies such as the Social Service and hundreds of villages in North Lampung. One of the applications used is SIKS-NG (Social Welfare Information System - Next Generation) which aims to facilitate the management of population data and community welfare programs. However, along with technological developments, data security is increasingly important to pay attention to. Cybercrime attacks, data leaks, and privacy violations are threats that must be taken seriously. The aim of this final assignment is to determine the extent of the security of the SIKS-NG application based on the results of COBIT 5 and ITIL V4 calculations and provide recommendations for improvements to increase information system security. The method used is the COBIT 5 and ITIL V4 method using the Align, Plan and Organize (APO13), Deliver, Support and Service (DSS05), Investment Management (IM14) domains. Data analysis uses the Capability Level, Maturity Level and Linkert Scale methods. The results of this research show that the Capability Level for the APO13 subdomain process obtained an average of 4.24 with a Gap of -0.24, DSS05 obtained an average value of 4.20 with a Gap of -0.20. From the overall results, the APO13 and DSS05 subdomain framework is at level 4 and has a Gap of -O.22, which means that at this level it shows that this subdomain has been achieved and fulfilled. Meanwhile, the Maturity Level for the IM13 subdomain process is on Scale 4 with an average value of 4.17 with a Gap of 0.83, which means it has not reached the target as expected. So this means that the security of the SIKS-NG application information system has the status of being well managed and must continue to be optimized, it's just that the program performance must be repaired and improved further. Keywords— System Security, COBIT 5, ITIL V4, Capability Level, Maturity Level